2015
DOI: 10.1590/0103-6440201300218
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Salicylate-based Pulp-Capping Material Containing Portland Cement

Abstract: The purpose of this study was to evaluate the water sorption, solubility, pH and ability to diffuse into dentin of a glycerol salicylate-based, pulp-capping cement in comparison to a conventional calcium hydroxide-based pulp capping material (Hydcal). An experimental cement was developed containing 60% glycerol salicylate resin, 10% methyl salicylate, 25% calcium hydroxide and 5% Portland cement. Water sorption and solubility were determined based on mass changes in the samples before and after the immersion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Many studies have focused on PC, which is compositionally similar to MTA, but less expensive. Several studies have suggested that PC is biocompatible and can be used as a safe pulp-capping material, and many PC-based materials have been investigated to meet clinical requirements 13 14 .…”
mentioning
confidence: 99%
“…Many studies have focused on PC, which is compositionally similar to MTA, but less expensive. Several studies have suggested that PC is biocompatible and can be used as a safe pulp-capping material, and many PC-based materials have been investigated to meet clinical requirements 13 14 .…”
mentioning
confidence: 99%
“…However, when this loss of mass is very significant, an empty space remains between the mineralized tissue and the restorative material. Thus, there is a need to achieve a balance between being soluble enough to have a therapeutic effect on the pulp tissue and not compromising the restorative procedure mechanically 40 .…”
Section: Discussionmentioning
confidence: 99%
“…stimulate pulp repair, dentin bridge formation, and its antimicrobial activity due from the high pH generated by the material [2][3][4][5][6] . However, calcium hydroxide-based cement shows several limitations, including rapid degradation, which is often incompatible with the repair time, the formation of tunnel defects in the dentin bridge, intense caustic, and inadequate sealing 7,8 .…”
mentioning
confidence: 99%